COPING STRATEGIES AMONG UNIVERSITY STUDENTS AND THEIR RELATIONSHIP WITH PARENTING STYLES - Hama, Rebwar G. (Journal of Sulaimani Medical College, 2023)
Background There is a strong correlation between parenting styles and the outcomes of adults; the most common coping mechanism was a spiritual connection. Objectives The present study aimed mainly at finding out the correlation between parenting styles and coping mechanisms and also to find out the most used parenting styles and coping mechanisms among the study sample. The study had a sub-aim of knowing the difference between the parenting styles perceived by the study sample compared with what has been found in the literature around the globe. Methods The study used a convenient sample of Koya University students who lived in the dormitories of the university campus. The sample comprised 411 students, 191 males and 220 females. For measuring the different styles of parenting and for measuring the different mechanisms of coping used by the study sample, a coping questionnaire was used. In addition, T-test and Pearson correlation techniques in Statistical Package for Social Sciences were also used to analyze the data frequency percentage. Results The study results showed a significant correlation between parenting styles and coping mechanisms; the passivity coping mechanism was positively correlated to the authoritative and permissive mothers’ parenting styles and positively correlated with the authoritative fathers’ parenting style. The population perceived the authoritarian parenting style to be the most used parenting style by both mothers and fathers. The most common coping mechanism among Koya University students was passivity. Conclusion The study findings indicated that the most used coping mechanisms by the study sample were passivity coping mechanisms, and the most common parenting style appraised by the study sample was the authoritarian parenting style.
Keywords: Coping strategies; Parenting Styles